Antimicrobial Sensitivity Trends of Carbapenem Resistant Acinetobacter Baumanii in Convalescents of Ventilator Associated Pneumonitis and other Specimens - Sonia Tahir, Kiran Fatima, Hina Javed, Nazia Ahmed, Sidrah Saleem, Saadia Chaudary (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the antimicrobial sensitivity trends of carbapenem resistant Acinetobacter baumanii in convalescents of ventilator associated pneumonitis and other specimens. Methods: In collaboration with Combined Military Hospital of Lahore a sum up of 47 hospital isolates of carbapenem resistant Acinetobacter baumanii were congregated. The microbial isolates re-confirmation was underwent by the morphological, cultural and biochemical approaches such as Grams method, inoculation on blood agar, oxidase reaction, mobility of organism, Analytical profile strips-20 NE. Result: Amongst 47 multidrug resistant isolates Acinetobacter microbes, it was found out that majority of specimens 38(81%) were from cases of ventilator associated pneumonitis, 3(6.3%) bacterial strain were from suppuration, 3(6.3%) from bloodline, 2(4.2%) were from urinary culture, in addition 1(2%) from bodily tissue. All the strains (n=47) were found to be Carbapenem resistant. Acinetobacter exhibited utmost opposition to number of antimicrobials, it was put on view that insensitivity levels equal to 100% (n=47) towards Cephems and the very closely related Carbapenems, microbicides such as Fluoroquinolones and Tazobactam group of ant microbes. One thing to be recorded was that the only drug of choice which showed least hostility against Acinetobacter was Tigecycline.